Sustainable Educational Organization: Education Management 4.0 Paradigms to Effectiveness of Basic Education Management Qualities - Jedaman, Pornchai; Yuenyong, Chokchai; Wichairam, Sathaporn; Khanewan, Prachan (Interdisciplinary Academic and Research Journal, 2023)
Education management paradigms an important in developing the educational organization’s quality to be successful. The objectives of this research are; (1) To study and analyze the educational management paradigm 4.0 that is effective for the quality of basic education management based on a sustainable educational organization. (2) To analyze the affirmative elements of the educational management paradigm 4.0 that are effective for the quality of basic education management on a sustainable educational organization basis. And (3) To study the direction of education management 4.0 that is effective for the quality of basic education management based on a sustainable educational organization. Is mixed method research in the study with primary and secondary education service area offices of 225 territories? The collections in qualitative came from a documentary study, the interview among 225 key informants of education area directors, and a quantitative survey by questionnaire among 480 samples of school directors and teachers study the data. Data were analyzed using basic statistics and confirmatory factor analysis (CFA). The results found that; the education management 4.0 paradigms of 10 factors as sceneries along with sustainable educational leadership, strategic education management, quality effectiveness management for sustainability, education management for security, education quality development for sustainability, building the education personnel to the highest potential for sustainable, creation of opportunities for access to standardized educational services for sustainable, education management based on participation for security, increasing the efficiency of educational management for sustainable, building a sustainable educational organization culture. By CFA of education management 4.0 paradigms to consistent with the empirical data at a statistical significance level of 0.01. And the directions of education management 4.0 include educational administration policy, administrators’ and teachers’ competencies, curriculum, and learning management, and providing a learning environment for the effectiveness of basic education management qualities based on sustainable educational organization.